Immediate Partial Breast and Nipple–Areola Complex Reconstruction Using a Superficial Circumflex Iliac Artery Perforator Flap - Gemma Pons; Lucía Sisternas; Jaume Masià (Archives of Plastic Surgery, 2024)
The superficial circumflex iliac artery perforator (SCIP) flap is a versatile flap that has been described for various applications, mostly for lower extremity coverage and head and neck reconstructions. However, there are few publications reporting its use for breast reconstruction, mainly because of its low volume availability. In this article, we present the case of a patient who successfully underwent a partial breast and immediate nipple–areola complex (NAC) reconstruction with an SCIP flap. She had been previously reconstructed with an implant after a nipple-sparing mastectomy, but the NAC turned out to be involved with cancer needing further resection. Our goal with this article, is to introduce a novel concept for addressing partial breast and NAC reconstruction and mostly, to illustrate the importance of an adaptable surgical plan based on every individual case emphasizing the versality of microsurgery for breast cancer reconstruction.